Seeds of Success: Collateral Benefits to Agricultural Crop Improvement, Research, and Education - Greene, Stephanie L.; Carver, Daniel; Khoury, Colin K.; Irish, Brian M.; Olwell, Peggy; Prescott, Leah (Wiley, 2019)
The need to restore natural landscapes impacted by environmental perturbations such as wildfires, and droughts, gave rise to Seeds of Success (SOS), a collaborative effort led by the Bureau of Land Management to collect seed of US wild native species since 2001. These collected native species are also important for agricultural activities; however, this has not been fully assessed. The SOS National Collection was evaluated for potential as sources of traits for crop improvement and direct development for agricultural purposes. Use of the collection was examined using information provided in seed requests from the USDA National Plant Germplasm System. From 2001 to 2017, SOS collected 23,577 accessions of 4761 different species, representing almost 30% of the native species in the United States. Collecting efforts have filled gaps in the conservation of native crop wild relatives; 12% of species and 18% of accessions are close and distant relatives of major and minor crops. Almost a third of the National Collection includes species with potential use in ornamental, food, medicinal, forage and feed, or material and industrial plant production. Of these species, those with ornamental potential are the most abundant in the National Collection. Requests for seed have been increasing over time, with the top three uses categorized as genetic studies, botanical or taxonomic investigations, and varietal development. Seeds of Success has positively affected the availability of native, wild plant genetic resources that have many potential uses in support of agricultural crop improvement, research, and education.